Building comprehensive mental health promotion in municipal settings. - Kasila, Kirsti; Tähkävuori, Jenni; Kilkku, Nina; Wallin, Outi; Tamminen, Nina (International Journal of Health Promotion & Education, 2026)
A comprehensive, promotion-oriented and multistakeholder approach to mental health promotion (MHP) is increasingly recognised as essential. This study, part of a larger participatory action research (PAR) project, explored how such an approach was implemented in six municipalities with one Finnish Wellbeing Service County. The municipalities acted as pilot areas, developing comprehensive, intersectoral MHP activities supported by local working groups and the research team. Following the pilot period, focus group interviews were conducted to gather participants' experiences, and the data were analysed using thematic analysis. The analysis identified five key themes for building comprehensive MHP: (1) Scope and commitment, (2) Management, resources and advocacy, (3) Value principles in practice, (4) Practice models and community events and (5) Collaboration and partnership. These elements reflect the core components of effective MHP and illustrate how local actors can co-create sustainable strategies through participatory processes. The study contributes to the growing body of research on capacity building in MHP. The findings offer practical insights for other regions and countries with similar municipal and public service structures, providing adaptable models for strengthening MHP through collaboration. Continued research and development are needed to further advance the implementation of comprehensive MHP approaches.